NYANYIAN RAKYAT ETNIK KAILI SEBAGAI PEMBINAAN KARAKTER BANGSA FOLK SONG KAILI’S AS NATIONS CHARACTER BUILDING - Deni Karsana; Wati Kurniawati; Aminah Aminah; Martina Martina; Wahyu Damayanti (Prosiding Seminar Nasional dan Internasional HISKI, 2023)
The Kaili ethnic has folk songs that are quite familiar to the people of Palu and its surroundings. However, at this time it is felt that Kaili's singing is starting to lose its prestige, especially among youths or teenagers. Actually, the Kaili folk song really entertained the people. Furthermore, behind the consolation, it turns out to have certain values that are good for character building. The method used in this paper is a qualitative descriptive method. The results showed that the Kaili ethnic folk song can be used as a good character building for the nation. The character building is in the form of educational values. The educational values contained in Kaili folk songs are religious, love for the homeland, cooperation, responsibility, friendship or communication, and obeying norms and rules.